Agent based interoperability in hospital information systems - Miranda, Miguel; Pontes, Gabriel; Abelha, Antonio; Neves, Jose; Machado, Jose (2012 5th International Conference on Biomedical Engineering and Informatics, 2012)
The healthcare area configures an environment of both complexity and cooperation. Numerous and distinct information systems must exchange information in a expedite and consolidated manner. Where healthcare interoperability is concerned numerous techniques, methodologies, architectures and standards exist, having also some which are more common. However subjects such as service distribution, fault tolerance, standards, communication flavoring and tightly-bound systems still are a major issue of concern. This paper aims to propose and explain a multi-agent based architecture which uses the HL7 standard as a means towards the implementation of interoperability in healthcare environment. It follows the concept of distributed consolidation of information, aiming heterogeneous systems to communicate towards their mutual benefit however through middleware agents which validate and consolidate information.